As condições de trabalho dos entregadores de empresas de plataformas digitais no Brasil e na Espanha: uma análise qualitativa por estudo de caso múltiplo. - Costa, Flora Oliveira da (2023)
This thesis presents a model for labor regulation in digital delivery platforms, focusing on labor law. Since digital platform companies utilize a business model sustained through freelance contracts, digital delivery work is associated with terrible working conditions, such as excessive and exhaustive work, lack of adequate places for food and rest, low salaries, and lack of collective bargaining. While disputes between companies and workers rise up to the highest labor courts, resolving the debate on working conditions requires verifying the employment relationship with its proper categorization, as employees. Thus, by proposing an alternative path to these obstacles, this study develops a regulatory model that makes the promotion of decent work viable. Through qualitative empirical research, this project aims to document the profile and working conditions of delivery drivers who are classified as salaried and selfemployed. This study is based on interviews with delivery drivers in two locations - Valencia, Spain and Recife, Brazil - to investigate whether the legal recognition of employment modifies working conditions. The project additionally conducts a literature review on the themes of capitalism, neoliberalism, legal subordination, and decent working conditions, which are explored throughout the various chapters of this thesis.